2003
DOI: 10.1161/01.res.0000091336.55487.f7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Stimulation of the eNOS Gene by the Stable Prostacyclin Analogue Beraprost Is Mediated Through cAMP-Responsive Element in Vascular Endothelial Cells

Abstract: Abstract-Beraprost sodium (BPS), an orally active prostacyclin analogue, has been reported to be beneficial in the treatment of primary pulmonary hypertension and obstructive peripheral arterial disease. Although BPS was originally described for its effects on platelet aggregation and vasodilatory response, the effect on endothelial cells has been poorly understood. In this study, we examined the effects of BPS on the eNOS gene expression in mouse aorta and cultured human and bovine aortic endothelial cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…46 In line with this, a fourfold increase in eNOS expression was found in cirrhotic as compared with noncirrhotic human livers. 47 Because bile salts are increased in cirrhosis and the promoter of the human eNOS contains a cAMP-responsive elements, 48 the increase in eNOS expression in cirrhotic livers may be partly mediated by the "bile salt-TGR5-cAMP pathway" as supported by our data. Apart from effects of NO on vascular resistance, NO may protect from oxidative stress and lipid peroxidation.…”
Section: Discussionsupporting
confidence: 72%
“…46 In line with this, a fourfold increase in eNOS expression was found in cirrhotic as compared with noncirrhotic human livers. 47 Because bile salts are increased in cirrhosis and the promoter of the human eNOS contains a cAMP-responsive elements, 48 the increase in eNOS expression in cirrhotic livers may be partly mediated by the "bile salt-TGR5-cAMP pathway" as supported by our data. Apart from effects of NO on vascular resistance, NO may protect from oxidative stress and lipid peroxidation.…”
Section: Discussionsupporting
confidence: 72%
“…In their physiological state, PGI2 and NO play complementary roles in vasodilation 56) . At the same time, PGI2 regulates the endothelial function via crosstalk with endothelial nitric oxide synthase (eNOS) 57) . This indicates that NO activates PGI2 synthase and increases PGI2 production 58) .…”
Section: Effects Of Pgi2 and Pgi3 On The Vascular Tonementioning
confidence: 99%
“…PGE 1 activates adenylate cyclase and increases intracellular cAMP via binding to prostanoid receptor subtypes EP2, EP3, EP4, and IP [31] . The cAMP-responsive elements (CRE) within the human eNOS promoter play an important role in the inducible expression of the human eNOS gene [32,33] . Progressive 5′-deletion and site-specific mutation analyses defined the beraprost-responsive sequences as CRE, located at -733 and -603 within the human eNOS promoter [32,33] , and the hypoxia- [34] , while the PGE 1 -responsive sequences are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 1 increases eNOS expression through PKA pathway activation and cAMPresponsive element binding protein (CREB) phosphorylation. Phosphorylated CREB predominantly binds to CRE, which leads to increased promoter activity and upregulation of the eNOS protein and mRNA expression [32][33][34] . Previous studies have also reported that PKA signaling increased phosphorylation of Ser-1177 and dephosphorylation of Thr-495 to activate eNOS, which led to the upregulation of NO [35] .…”
Section: Discussionmentioning
confidence: 99%